THIAMINE-RESPONSIVE MEGALOBLASTIC ANAEMIA WITH HYPOTHYROIDISM, A PUZZLING ASSOCIATION - Versha Rani Rai; Mohsina Noor Ibrahim; Muhammad Nasir Javed; Khoso, Zubair; Heeranand Rathore (Journal of Ayub Medical College Abbottabad, 2024)
Background: Thiamine-responsive megaloblastic anemia (TRMA) is characterized by the classic trio of diabetes mellitus, sensorineural hearing loss, and megaloblastic anemia, typically emerging subtly between infancy and adolescence. Administration of high-dose thiamine often yields improvements in anemia and occasionally in diabetes. Uncommon manifestations include optic atrophy, congenital heart defects, short stature, and stroke. In this specific case, a 5-year-old diagnosed with insulin-dependent diabetes mellitus (IDDM) since the age of one presented with symptoms such as polyuria, fever, and vomiting, revealing an HbA1c of 10.64. Further examinations disclosed compromised hearing and vision. Negative antibody workup and a thyroid profile indicating hypothyroidism prompted additional investigations, including Brainstem Evoked Response Audiometry (BERA) and retinal examination, confirming bilateral sensorineural hearing loss and maculopathy, respectively. A comprehensive blood count unveiled megaloblastic anemia. Genetic profiling confirmed a homozygous mutation in the SLC19A2 gene, thus diagnosing TRMA. An early diagnosis, coupled with genetic confirmation, enables timely intervention, with patients responding positively to high-dose thiamine. Genetic counseling plays a pivotal role in enlightening families about the disease and its inheritance patterns, fostering awareness and understanding.